Maize chloroplast RNA polymerase: the 78-kilodalton polypeptide is encoded by the plastid rpoC1 gene. - Hu, J (1991)
The 180-, 120- and 38-kDa polypeptides found in highly purified maize plastid RNA polymerase preparations are encoded by the maize plastid genes rpoC2, rpoB, and rpoA, respectively [Hu, J. and Bogorad, L. (1990) Proc. Natl. Acad. Sci. USA. 87, pp. 1531-1535]. These genes have segments that specify amino acid sequences homologous to those of E. coli RNA polymerase subunits. The plastid gene products are designated b", b and a, respectively. We report here that the amino-terminal amino acid sequence of a 78-kDa polypeptide also found in highly purified maize plastid RNA polymerase preparations matches precisely the sequence deduced from the maize plastid rpoC1 gene which has segments homologous to the 5' end of the E. coli rpoC gene. Thus, the 78-kDa polypeptide is likely to be a functional component of maize plastid DNA-dependent RNA polymerase. This polypeptide is designated subunit b'. Three polypeptides unrelated to RNA polymerase have also been identified in this preparation.